Difusi inovasi cerita prosa rakyat dalam aplikasi audiobuku - Evi Nursanti Rukmana; Pawit M. Yusup; Wina Erwina (IAIN Padangsidimpuan, 2019)
The folklore is a story in all-region as documentation of culture in the community. In the information community, people to need activities in the reading with easy and fast to use. AudioBuku is an application in handphone (HP) that has a collection of folklore at Indonesia. The purpose this research is to know diffusion of innovation the folklore in AudioBuku, consist of a process of innovation, a process of diffusion, and a process of adoption. The method this research used qualitative methods approach with case study method. The result this research is in the innovation process, the feature of AudioBuku can to direct the children’s to listen to audio the folklore. The folklore collection is free and unfree to access. In process of diffusion, AudioBuku media on HP can be access by the children and the parents. In the adoption process, more of the children and the parents as a sustainable adoption and adoption. They can to use AudioBuku continuously or an only certain time. AudioBuku has serve facilitate education consist of audio media to use in reading activities.